Age-related macular degeneration: an overview - de Almeida Torres, Rogil José [UNESP]; dos Anjos Ferreira, Ana Lúcia [UNESP] (Revista Brasileira de Oftalmologia, 2021)
Age-related macular degeneration is the most important cause of irreversible vision loss in the elderly and has been considered a severe public health problem. Current treatments have only been successful in delaying the loss of central vision. Due to increased life expectancy, governments and researchers have been challenged to seek more efficient and successful treatments for age-related macular degeneration. Considering its relevance for public health and the need of further research, this article aims to address age-related macular degeneration objectively, tackling on the current knowledge about its pathophysiology, potential molecular biomarkers, main prevention procedures and treatments, as well as introducing possible molecules that may be a therapeutic target in this disease.
Degeneração macular relacionada ã idade: um panorama geral
Keywords: Biomarkers; Inflammation; Macular degeneration; Oxidative stress; Primary prevention; Retinal pigment epithelium; Secondary prevention